2008
DOI: 10.1111/j.1467-6451.2008.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

OVERSEAS R&D ACTIVITIES AND HOME PRODUCTIVITY GROWTH: EVIDENCE FROM JAPANESE FIRM‐LEVEL DATA*

Abstract: This paper investigates the impact of overseas subsidiaries' R&D activities on the productivity growth of parent firms using firm-level data for Japanese multinational enterprises. Based on survey responses, we classify each overseas subsidiary's R&D as either 'innovative R&D,' which we hypothesize is likely to lead to the acquisition of foreign knowledge, or 'adaptive R&D,' which is more likely to lead to adaptation to local conditions. We find that overseas innovative R&D raises the parent firm's productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 36 publications
(43 reference statements)
0
43
0
Order By: Relevance
“…Fors (1997), using Swedish firm data, did not find any significant productivity effect. On the other hand, Todo and Shimizutani (2008) showed, based on firm-level data for Japanese multinational enterprises, that overseas "innovative" R&D (aiming at the acquisition of foreign knowledge) raises the parent firms' productivity growth, while "adaptive" overseas R&D (aiming at the adaptation of products/technologies to local conditions in foreign locations) has no such effect. Griffith et al (2004) identified positive productivity effects of knowledge-sourcing.…”
Section: Foreign Randd Activities and Economic Performance Of The Parenmentioning
confidence: 99%
“…Fors (1997), using Swedish firm data, did not find any significant productivity effect. On the other hand, Todo and Shimizutani (2008) showed, based on firm-level data for Japanese multinational enterprises, that overseas "innovative" R&D (aiming at the acquisition of foreign knowledge) raises the parent firms' productivity growth, while "adaptive" overseas R&D (aiming at the adaptation of products/technologies to local conditions in foreign locations) has no such effect. Griffith et al (2004) identified positive productivity effects of knowledge-sourcing.…”
Section: Foreign Randd Activities and Economic Performance Of The Parenmentioning
confidence: 99%
“…Higon et al (2011) obtain a positive output effect of foreign R&D in the case of UK multinationals. Other studies also find a positive effect, which, however, is only due to specific categories of foreign R&D. For example, Todo and Shimizutani (2008) show, for Japanese companies, that overseas R&D which aims at the acquisition of new knowledge increases the growth of total factor productivity (TFP), but that this is not the case for R&D which focuses on the adaptation of products to foreign market needs. In contrast to Japan, in the case of Switzerland the positive impact on labour productivity is the result of market-and efficiency-seeking foreign R&D, while knowledge-seeking R&D does not have such an effect (Arvanitis and Hollenstein 2011).…”
Section: Impact On Productivitymentioning
confidence: 95%
“…R&D conducted in foreign affiliates has traditionally focused on the adaptation of home-developed technologies to foreign markets ('home base exploiting' or 'adaptive' R&D), but the evidence suggests that it has also become a vehicle to access foreign technological and scientific strengths and to create new technologies ('home base augmenting' or 'innovative' R&D) (Kuemmerle 1997;Von Zedtwitz and Gassmann, 2002;Shimizutani and Todo, 2008;Griffith et al, 2008;Belderbos, 2003;Belderbos et al, 2009;Penner Hahn and Shaver, 2005). Although empirical studies examining the determinants of foreign 6 R&D have uncovered a number of host country factors affecting R&D investments (e.g.…”
Section: Introductionmentioning
confidence: 99%